A Larger Frame: “Redressing” the Image of Doukhobor-Canadian Women in the Twentieth Century - Androsoff, Ashleigh (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2007)
AbstractThe image of a naked “Doukhobor” woman standing before her flame-engulfed home has been used repeatedly to embody the Doukhobors’ difficult adjustment to life in Canada. Here, the author argues that public attention on Doukhobor women’s bodies predates the publication of nude imagery in the middle of the twentieth century. A review of twentieth-century descriptions of Doukhobor-Canadian women reveals that their bodies were subjected to intense public scrutiny from the moment they arrived in Canada in 1899. Publishing descriptions and photographs of Doukhobor women engaged in hard farm labour, doing “women’s work,” wearing traditional ethnic dress, and in partial or total states of undress, the Canadian media significantly shaped “public knowledge” about the Doukhobors by focusing on the peculiarity of Doukhobor women’s bodies.